PELATIHAN DAN PENDAMPINGAN MONTESSORI BAGI GURU DAN SISWA TK KANISIUS IMMAKULATA SURAKARTA - Andri Anugrahana (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Implementation of Community Service is divided into two programs, Training intended for teachers and Mentoring for kindergarten students. The trainer in this Community Service is lecturer and mentor for kindergarten students are PGSD students who are members of the Montessori Club. Lecturers provide training for teachers, while students provide assistance to kindergarten students. The purpose of this Community Service are to improve and to assist in the education process especially at the elementary level and in the early age level, while also providing experience for lecturers in training teachers and experience for PGSD students in assisting early students. Community Service procedures are (1) conducting a needs analysis, (2) designing training, (3) coordinating, (4) conducting training, (5) evaluating training, (6) writing Community Service articles. Outcomes in this Community Service are (1) training by lecturer, (2) mentoring Kindergarten students by PGSD students, (3) Community Service report articles.